MUSEUM SUNGAI DI BANJARMASIN - Muhammad Rizqan Anwari; J.C Heldiansyah (ULM Press, 2021)
The river museum in Banjarmasin is a place to capture the existence of rivers in Banjarmasin. The existence of rivers decrease in function and existence until it turns into a dead river. The river's existence is influenced by river culture. River culture is formed by people whose lives depend on rivers. Therefore, to preserve the information related to this matter, efforts are made by preserve and communicate it to the public by create a river museum.To create a river museum, the point of view concept is used which tells the museum narrative based on time, place, and actor. This concept is supported by the application of the sense of place method. Thus, river museums can make visitors educated and empathize with rivers in Banjarmasin.